Assessment of Parents Anxiety within Safety of Children: Primary schools in the upper southern part of Thailand - Kirati Sattanon; Prapatpong Upala (My University, 2017)
The objectives of this paper are to investigate the parental anxiety within the safety of children travel to school and examine the student's self-help abilities. The 1,105 questionnaires were sent to caretakers through pupils. The results indicated that their worries at the high level mainly about the school setting, traffic volume, weather, security management, and facilities. Additionally, these worries are different from socio-economics, family’s characteristic and physical environment. Furthermore, the gender, family incomes and grade of students cause a greater level of safety concern. Finally, the needs to improve the school are (1) Traffic management, (2) Safety Zone and (3) Facilities.Keywords: Anxiety; Safety; Parent; Children; Kindergarten.ISSN: 2398-4287© 2017. The Authors. Published for AMER ABRA by e-International Publishing House, Ltd., UK. This is an open access article under the CC BYNC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/). Peer–review under responsibility of AMER (Association of Malaysian Environment-Behaviour Researchers), ABRA (Association of Behavioural Researchers on Asians) and cE-Bs (Centre for Environment-Behaviour Studies), Faculty of Architecture, Planning & Surveying, Universiti Teknologi MARA, Malaysia.
Keywords: Early Childhood Education and Development